Zooplankton community composition and some limnological aspects of an oxbow lake of the Paraopeba River, São Francisco River Basin, Minas Gerais, Brazil - Sampaio,Edson Vieira (2000)
Some limnological aspects of Lake Massacará (adjoining the Paraopeba River, São Francisco River Basin) were studied during two periods of the hydrological cycle. Water transparency was equally low during both the periods. During high water, thermal stratification was recorded, with a clinograde oxygen profile; pH was slightly acid, and conductivity was higher near the bottom. Concentrations of inorganic carbon and ammonia, and rates of primary production were higher than during the low water period. During the latter period, complete mixing occurred, with a clinograde oxygen profile; pH was slightly acid, and conductivity unvarying with depth. Higher concentrations of nitrate were found than during high water. With regard to the zooplankton communities, higher density and species richness of organisms occurred during high water. Copepods and rotifers were most numerous during both periods. The taxa identified consisted of 17 rotifers, four copepods, six cladocerans, five protozoans, and two macroinvertebrates. The most abundant species were Thermocyclops minutus, Keratella cochlearis, K. lenzi, and Trichocerca capucina during high water, and Thermocyclops minutus and Conochilus unicornis during low water.